Pregnancy-associated cancers: frequency and temporal trends in Italy. Issue 2 (19th November 2019) - Parazzini, Fabio; Gadducci, Angiolo; Cicinelli, Ettore; Maggino, Tiziano; Peccatori, Fedro; Scarfone, Giovanna; Roncella, Elena; Scambia, Giovanni; Zola, Paolo; Sartori, Enrico
Abstract : Objective: Limited data are available on the frequency and time trends of pregnancy-associated cancers, particularly from Southern European countries. The aim of this study was to analyze the frequency and time trends of pregnancy-associated cancer in Italy. Methods: This was a population-based linkage study using the regional hospital discharge forms database of four Italian regions with more than 17 million inhabitants. All resident women with a hospital discharge form reporting a birth or abortion in the time period under consideration were identified. The time period of the study was 2003–2015 for the Piemonte and Puglia region, 2006–2015 for the Tuscany region, and 2005–2015 for the Veneto region. Risk of developing a pregnancy-associated cancer was calculated as the ratio of the number of pregnancy-related cancers to the total number of pregnancies. Results: A total of 2 297 648 pregnancies were identified. Overall, the pregnancy-associated cancer frequency was 134.8 per 100 000 pregnancies: the frequency ranged from 127.1 in Puglia to 157.3 in Tuscany. The frequency for 100 000 pregnancies was 66.4 in women aged <30 years; the risk increased with age, with a frequency of 275.6 among women aged 40+ years. Approximately two-thirds of cancers were associated with pregnancies resulting in a delivery and one-third with pregnancies resulting in a termination of pregnancy or spontaneous pregnancy loss. No clear trend emerged in the risk of pregnancy-associated cancer per 100 000 pregnancies and calendar year. Conclusion: No clear time trend was observed in the frequency of pregnancy-associated cancers in Italy during the last 10 years, the rates being 104, 164, and 130 per 100 000 pregnancies, respectively, in 2003, 2010, and 2015.